UMA METODOLOGIA PARA ALOCAÇÃO DE PERDAS ATIVAS DE TRANSMISSÃO EM AMBIENTE COMPETITIVO - Santos Junior, Bartolomeu Ferreira dos (2007)
The goal of loss allocation methodologies is to share the responsibility for transmission losses among generators and loads. Several loss allocation methods have been developed to solve this problem. However, there is not consensus regarding to the most appropriated approach methodology. There are some methods presenting suitable accuracy, however, still remains the equity question. It can say that there isn t an ideal method, although it is desirable that any method achieve efficient allocation criteria. In this work, it is proposed a methodology for active power transmission loss allocation, based on circuit laws, proportional sharing and superposition principles. The methodology uses a load flow solution to share the global loss of the system among market participants. The problem is divided into operation scenarios and taking into account transmission paths used by generators to supply the loads. Tests, analyses and comparison with some methods proposed in literature are performed, using a five bus test system, and IEEE 30 and IEEE 118 systems.